Analysis of Iron (Fe) and Zinc (Zn) in Red Fruit (Pandanus conoideus De Vriese) - Alizah, Nur; Walanda, Daud K; Hamzah, Baharuddin (Universitas Tadulako, 2019)
Red fruit plant (Pandanus conoideus De Vriese) is very potential for health. This is because the plant contains many nutrients, especially minerals that are needed for the human body. Iron and zinc are two micro-minerals that contained in red fruit, but the content data about those are not widely known. The aim Â of this research was to determine iron and zinc content by atomic absorption spectrophotometric of red fruit fromÂ Mattirowaslle Village, South Pamona Sub-district, Poso Regency, Central Sulawesi. The water content of the sample obtained was 52%, and the ash content was 13.8%. While the analysis of iron and zinc content at wavelength 248.30 nm (iron) and 213.90 nm (zinc) obtained were 1,339 mg/100g for iron and 0,397 mg/100g for zinc.